2018
DOI: 10.2174/1874613601812010069
|View full text |Cite
|
Sign up to set email alerts
|

“Too Much Sex and Alcohol”: Beliefs, Attitudes, and Behaviors of Male Adolescents and Young Men Who have Sex with Men in Ghana

Abstract: Background:Research suggests that men who have sex with men (MSM) often engage in high-risk sex and use illicit substances.Objective:To increase understanding of HIV knowledge and vulnerability among adolescent and young adult MSM, with a focus on alcohol and drug use and transactional sex.Methods:We conducted in-depth interviews and Focus Group Discussions (FGDs) with adolescent (aged 15-17 years) and young adult (aged 18-29 years) MSM in Kumasi, Ghana. MSM who reported recent alcohol and/or substance use or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In this paper, we describe the use of the ADAPT-ITT model in the adoption and adaptation of the 3MV with MSM in Ghana. Despite the existing disproportionate infection rates of HIV among MSM and its association with existing structural factors (such as criminalization and stigma against MSM), and individual-level factors (such as sex without a condom, and transactional sex) in Ghana and other sub-Saharan African countries, only a few scholars consider intervention as an approach to reducing HIV and STI risk among MSM in the country (Koblin et al, 2006;Baral et al, 2011;Cloete et al, 2013;Logie et al, 2012;Park et al, 2013;Sabin et al, 2018). As such, in collaboration with community partners, we engaged MSM through the use of the ADAPT-ITT model (Table 1) to adapt the 3MV (Table 2) to address HIV and STD risk factors and contribute to reducing HIV infections (Abubakari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we describe the use of the ADAPT-ITT model in the adoption and adaptation of the 3MV with MSM in Ghana. Despite the existing disproportionate infection rates of HIV among MSM and its association with existing structural factors (such as criminalization and stigma against MSM), and individual-level factors (such as sex without a condom, and transactional sex) in Ghana and other sub-Saharan African countries, only a few scholars consider intervention as an approach to reducing HIV and STI risk among MSM in the country (Koblin et al, 2006;Baral et al, 2011;Cloete et al, 2013;Logie et al, 2012;Park et al, 2013;Sabin et al, 2018). As such, in collaboration with community partners, we engaged MSM through the use of the ADAPT-ITT model (Table 1) to adapt the 3MV (Table 2) to address HIV and STD risk factors and contribute to reducing HIV infections (Abubakari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HIV stigma in Sub-Saharan Africa leads to guarded disclosures which are disruptive to HIV testing and early linkage to care [ 21 , 24 ]. Qualitative studies in Ghana found same-sex stigma undermines HIV testing for MSM [ 7 ] and was a barrier to seeking general health and HIV testing services [ 25 ]. Within HCFs, negative interactions with staff can discourage MSM from seeking HIV testing or disrupt linkage to care [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies in Ghana found same-sex stigma undermines HIV testing for MSM [ 7 ] and was a barrier to seeking general health and HIV testing services [ 25 ]. Within HCFs, negative interactions with staff can discourage MSM from seeking HIV testing or disrupt linkage to care [ 25 ]. At the interpersonal and individual levels, perceived stigma can lead MSM to avoid health care services due to fear that someone will discover they have sex with men [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for heavy alcohol use reported by GBMSM in general may include life histories of traumatic experiences such as sexual orientation-based discrimination and childhood sexual abuse [ 38 , 39 ], while YMSM specifically reported social drinking motivations as a main reason for engaging in heavy alcohol use [ 40 ]. As for the use of alcohol during sex among GBMSM, reasons included more situational or contextual factors such as the facilitation of cognitive ‘escape’ for the awareness of HIV risk, or the enhancement of sexual pleasure [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%